MINERALOGY CHARACTERS OF CIJULANG PHOSPHATE ROCKS RELATED TO BIOLEACHING PROCESS - Tatang Wahyudi; Erwin Faizal (Puslitbang tekMIRA, 2016)
Research on potency test of selected phosphate solubilizing microfungi (PSM) isolates had been conducted. The purpose was to obtain the most potential indigenous microfungi to solubilizing phosphate in bioleaching process. Identification with moist chamber showed that the selected PSM belonged to Penicillium genera. Bioleaching process through measuring process growth and oxalic acid production was effective on the 8th day. Chemical analysis showed that bioleaching process using selected indigenous PSM of phosphate rock was able to increase P2O5 content from 38.40 to 49.70% or improve around 11.30%. Experimental condition for such a recovery was -140+200# of sample size an 5% of percent solid. Mineralogy characters of the leached phosphate rocks showed some micro cracks as well as encapsulation by clay minerals. Not all phosphor element was leached by oxalic acid produced by microfungi.